Environmentally-friendly strategy for separation of 1, 3-propanediol using biocatalytic conversion. (December 2017) - cui, Caixia; Zhang, Zhe; Chen, Biqiang
Graphical abstract: Highlights: An entire enzymatic route for separating 1, 3-propanediol was established. Method for separating 1, 3-propanediol is simple, efficient, and environmentally-friendly. 1, 3-Propanediol recovery efficiency reached 96%. 1, 3-Propanediol can be efficiently separated with 2, 3-butanediol and glycerol using lipase. Abstract: Glycerol waste from the biodiesel production can be used as a carbon source in the production of 1, 3-propanediol (1, 3-PD) through microbial fermentation. However, downstream processing is a major bottleneck that restricts its biological production. Here, we investigated an environmentally-friendly method to enzymatically separate 1, 3-PD. The transformation of 1, 3-PD to an ester was achieved by exploiting the esterification reaction with fatty acids under lipase catalysis. The reaction efficiency was optimized using different poly-alcohols that were existed in the fermentation broth reacted with a fatty acid. Whereas the 1, 3-PD conversion reached 62%, only a 0.06% and 0.08% conversion was reached for 2, 3-butanediol and glycerol, illustrating the former's more efficient separation. The recovery efficiency of 1, 3-PD was 96%. Finally, 1, 3-PD was obtained by lipase-directed ester hydrolysis. Taken together, the bio-catalyzed separation process presented here is a novel and promising method for recovering 1, 3-PD.